« Condamnés à mort » : les mots français de Walter Pater - Bénédicte Coste (Cahiers Victoriens et Edouardiens)
This article focuses on the use of French words, expressions and citations in Walter Pater’s The Renaissance (1873), be they translated or not. Pater’s scholarly use of foreign languages pertains to the Decadent rhetoric; however his precise use of them as well as the effects he creates are specific to Pater who adroitly masks his sources or pinpoints them by a masterly use of foreign words. If, for him, words express the otherness of any tongue and the process of translation that is involved in using it, the French words of The Renaissance more especially designate the otherness of death.